Modern Slavery A Comparative Study of the Definition of Trafficking in Persons - Borg Jansson, Dominika (Brill, 2014)
In Modern Slavery - A Comparative Study of the Definition of Trafficking in Persons Dominika Borg Jansson discusses why, despite international anti-trafficking efforts, there are so few trafficking convictions worldwide. In an easily accessible language, the author explains why international legal harmonization in this area has been difficult. Making use of the concept of legal transplants, Dominika Borg Jansson compares experiences from Sweden, Poland and Russia offering insights into especially Russian legislation that are not widely available. The problems concerning the implementation of the international definition of trafficking are here divided into country-specific challenges and obstacles attributable to the original source. Jansson also addresses the effectiveness of criminalization of trafficking and offers suggestions on how future trafficking legislation might be framed.